The resurgence of the Adora2b receptor as an immunotherapeutic target in pancreatic cancer - Strickland, Lincoln N.; Faraoni, Erika Y.; Ruan, Wei; Yuan, Xiaoyi; Eltzschig, Holger K.; Bailey-Lundberg, Jennifer M. (Frontiers in Immunology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by a dense desmoplastic stroma that impedes drug delivery, reduces parenchymal blood flow, and suppresses the anti-tumor immune response. The extracellular matrix and abundance of stromal cells result in severe hypoxia within the tumor microenvironment (TME), and emerging publications evaluating PDAC tumorigenesis have shown the adenosine signaling pathway promotes an immunosuppressive TME and contributes to the overall low survival rate. Hypoxia increases many elements of the adenosine signaling pathway, resulting in higher adenosine levels in the TME, further contributing to immune suppression. Extracellular adenosine signals through 4 adenosine receptors (Adora1, Adora2a, Adora2b, Adora3). Of the 4 receptors, Adora2b has the lowest affinity for adenosine and thus, has important consequences when stimulated by adenosine binding in the hypoxic TME. We and others have shown that Adora2b is present in normal pancreas tissue, and in injured or diseased pancreatic tissue, Adora2b levels are significantly elevated. The Adora2b receptor is present on many immune cells, including macrophages, dendritic cells, natural killer cells, natural killer T cells, γδ T cells, B cells, T cells, CD4+ T cells, and CD8+ T cells. In these immune cell types, adenosine signaling through Adora2b can reduce the adaptive anti-tumor response, augmenting immune suppression, or may contribute to transformation and changes in fibrosis, perineural invasion, or the vasculature by binding the Adora2b receptor on neoplastic epithelial cells, cancer-associated fibroblasts, blood vessels, lymphatic vessels, and nerves. In this review, we discuss the mechanistic consequences of Adora2b activation on cell types in the tumor microenvironment. As the cell-autonomous role of adenosine signaling through Adora2b has not been comprehensively studied in cancer cells, we will also discuss published data from other malignancies to infer emerging therapeutic considerations for targeting the Adora2b adenosine receptor to reduce the proliferative, invasive, and metastatic potential of PDAC cells.